Аналіз та перспективи імплементації в Україні європейських норм та стандартів якості адміністративно-правової охорони навколишнього природного середовища в умовах сьогодення - Казанчук, І. Д.; Kazanchuk, I. D.; Казанчук Ірина Дмитрівна (Актуальні питання у сучасній науці. - 2022. - № 6(6). - С. 108-119, 2022)
Проведено аналіз адміністративно-правових норм та стандартів якості охорони навколишнього природного середовища, які діють у Європейському Союзі. Визначено можливості імплементації норм Європейського права в адміністративне законодавство України, а також європейських стандартів якості в діяльність уповноважених державних органів в природоохоронній сфері.

The article at the theoretical and legal level analyzes the administrative and legal norms and quality standards of environmental protection that operate in the European Union.The article draws attention to the peculiarity of the EU administrative legislation on environmental protection, which consists of separategroups of norms that regulate the protection of living nature, the issue of combating air and noise pollution, limiting chemical pollution and waste disposal, the issue of fighting for water purity, etc.In general, the general environmental policy of the EU is connected with the adoption and implementation of six Action Programs, on the basis of which the normative legal acts of the European Community on the protection of the natural environment in various spheres of life of the member countries have been prepared. It is also indicated that the system of standards in the European Union in the field of environmental protection is established primarily in EU directives. To date, more than 90 directives have been adopted in the field of environmental protection.The author concluded that the main idea of the process of improving the nature protection sphere in Ukraine should be the national legal framework in the field of environmental protection, harmonized with European legislation, and the improvement of the institution of administrative responsibility of individuals and legal entities for causing damage to the surrounding natural environment.The author also pointed out that in Ukraine there is a need to: 1) improve the legal mechanism for providing the public with information on environmental protection issues, as well as public participation in decision-making related to environmental safety and the implementation of environmental protection measures; 2) development and implementation of state and regional programs for the spread of eco-education in society; 3) improvement of international cooperation of law enforcement agencies of Ukraine and EU member states with the aim of exchanging best practices and methods of environmental protection activities; 4) development and implementation of the concept of formation of ecological culture of the population of Ukraine.

Проведен анализ административно-правовых норм и стандартов качества охраны окружающей среды, действующих в Европейском Союзе. Определены возможности имплементации норм Европейского права в административное законодательство Украины, а также европейских стандартов качества в деятельность уполномоченных государственных органов в природоохранной сфере.
Analysis and prospects of implementation in Ukraine of european norms and quality standards of administrative and legal environmental protection in today's
Keywords: Адміністративне право та процес. Administrative Law and Procedure. Административное право и процесс; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; адміністративно-правові норми; administrative and legal norms; административно-правовые нормы; Європейській Союз; European Union; Европейский Союз; охорона навколишнього природного середовища; environmental protection; охрана окружающей природной среды; імплементація; implementation; имплементация; європейські стандарти; European standards; европейские стандарты; природоохоронні органи; nature protection authorities; природоохранные органы